Geochemical properties in riverbed sediments on the Malay Peninsula and surface sediments of western Sunda Shelf - Bingbing Wei; Guodong Jia (PANGAEA, 2024)
In August 2018, 10 riverbed sediments and 12 marine surface sediments were collected from the Kelantan and Pahang Rivers as well as the adjacent Sunda Shelf using a grab sampler. These sediment samples were analyzed using biogeochemical markers to assess the dispersal and burial of terrigenous organic carbon (OC) from the Malay Peninsula on the western Sunda Shelf. The bulk OC content is measured using an element analyzer, and δ13C of OC is obtained by isotope ration mass spectrometer. Additionally, lipid biomarkers are extracted, separated, and quantified with wet chemical perpetrations of diols and GDGTs. This dataset includes organic carbon (OC) content, δ13C of OC, terrestrial OC proxies (BIT, #ringstetra, ΣIIIa/ΣIIa and %C32 1,15+%C28 1,13 values), calculated fraction and content of terrestrial OC in riverbed sediments from the Malay Peninsula and surface sediments from the western Sunda Shelf. Detailed dataset interpretation can be found in Wei et al. (2024).